(untitled) (Economics and region, 2019)
For Ukraine the issue of renewable energy development is extremely relevant in view of energy (increase in energy independence), economic (reduction of energy resources import costs), environmental (reduction of environmental pollution) and social (improvement of energy supply, increase in income of the population) problems that can be solved at its expense. Based on the existing potential, if there exist adequate mechanisms of government support for the renewable energy development, Ukraine may increase the share of renewable energy sources in the energy balance up to 25% by 2035, reducing to import a significant share of energy resources. In order to justify the economic feasibility of investing in households’ renewable energy projects until 2029 and to identify the promising trends in this sector development in Ukraine, the authors have assessed the economic efficiency of a project of 10 kW solar power plant construction in a typical Ukrainian household under some conditions. The results have shown that it is expected to observe a gradual outflow of investments from renewable energy sector of households since 2022-2023 due to the decrease in feed-in tariff rates and a corresponding decrease in the profitability of private renewable energy projects with small power capacities. Therefore an alternative powerful state support will be needed to provide the development of renewable energy sector.